Analysis of the Reforms to the Academic Regime Regulation and their Impact on Curriculum Redesign in Undergraduate Programs in Ecuador - Compte Guerrero, Maria; Sánchez del Campo Lafita, Martha Maria (Revista Ecos de la Academia, 2024)
With the purpose of analyzing how the multiple reforms of the Academic Regime Regulation, approved by the Council of Higher Education, CES, have affected the redesign of degree courses in Higher Education Institutions, IES, a qualitative investigation was carried out on the regulatory provisions proposed for third-level degree courses, bachelor’s degrees and engineering and architecture in terms of academic periods, hours and credits of the courses, and how these reforms have influenced the redesign of the respective curricula. The methodology followed to meet this objective was a documentary review of the aforementioned regulations and their versions, in addition to certain studies related to curricular reforms and the aspects to be considered.